The Impact of Macroeconomic Variables on the Contingent Built-in Inflation: Evidence from Indonesia - Prabhanshu Sharma; Mohammad Rashed Yadgari (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
This paper examines the relationship between Exchange rates, GDP, and Government expenditure as macroeconomic variables on the Inflation of Indonesia which is quite struggling with increased prices of goods and services as it has been a persistent problem in Indonesia for many years. In 2023, it is so far 5.47% which is above the target set by the central bank of Indonesia of 2-4%. With the data taken from World Bank and IMF, the methodology consists of stationarity check, Cointegration analysis, and Error Correction Model to identify the long-run nexus among variables. The estimation result found that GDP is positively correlated with Inflation, Exchange rate is positively correlated with mild effects on inflation and government expenditure is negatively correlated with Inflation.